Traumatic brain injured patients: primum non nocere. Issue 5 (October 2018) - Wijayatilake, Dhuleep S.; Nielsen, Dominic P.D.; Baker, Elinor; Patil, Vinod
Abstract : Purpose of review: Traumatic brain injury (TBI) remains an unfortunately common disease with potentially devastating consequences for patients and their families. However, it is important to remember that it is a spectrum of disease and thus, a one 'treatment fits all' approach is not appropriate to achieve optimal outcomes. This review aims to inform readers about recent updates in prehospital and neurocritical care management of patients with TBI. Recent findings: Prehospital care teams which include a physician may reduce mortality. The commonly held value of SBP more than 90 in TBI is now being challenged. There is increasing evidence that patients do better if managed in specialized neurocritical care or trauma ICU. Repeating computed tomography brain 12 h after initial scan may be of benefit. Elderly patients with TBI appear not to want an operation if it might leave them cognitively impaired. Summary: Prehospital and neuro ICU management of TBI patients can significantly improve patient outcome. However, it is important to also consider whether these patients would actually want to be treated particularly in the elderly population.